PKIoT: A public key infrastructure for the Internet of Things. Issue 10 (8th July 2019) - Marino, Francesco; Moiso, Corrado; Petracca, Matteo
Abstract: Internet of Things (IoT) nodes participating in the implementation of next‐generation IoT applications will need standard methods to authenticate each other and secure their communications. However, the use of certificates and public key infrastructure (PKI) technologies, widely employed in the Internet, is not straightforward in this context because of the limitations of the involved entities. This paper presents the public key infrastructure for the Internet of Things (PKIoT) architecture, a solution which aims at enabling certificate‐based authentication in the forthcoming IoT scenarios by allowing the flexible outsourcing of the most demanding security‐related tasks and by introducing a new type of compact certificate. This paper also highlights the role that this architecture can play in the context of the oneM2 M security framework in enabling standard secure machine‐2‐machine interactions. In conclusion, this paper reports the results of the conducted experiments, which show the effectiveness of the proposed approach in reducing the execution time and the energy consumption of certificate‐based session establishment for Datagram Transport Layer Security up to 78% and 89% respectively, fostering this way standard and secure IoT transactions. Abstract : The paper proposes the PKIoT architecture as a solution to enable certificate‐based authentication in the IoT context by allowing the flexible outsourcing of the most demanding security‐related tasks. The paper also highlights the role that this architecture can play in enabling standard secure M2M transactions in the oneM2M security framework. The conducted experiments show that the proposed approach can reduce the execution time and the energy consumption of certificate‐based DTLS session establishment up to 78% and 89% respectively.